The Effect of Writing Novel Reviews on English Education Students' Writing Ability - Aulia Qory Fadhilla; Faras Salwa Qadisia; Arina Fauzia; Lisa Anggita; Ummi Kultsum (EDUKATIF : JURNAL ILMU PENDIDIKAN, 2023)
Writing is considered one of the most complex skills because writing is a creative process that must always be practiced to produce good written works; one way to practice this skill is by writing novel reviews. Although many studies have explored the correlation between reading novels and improving writing ability, limited attention has been directed to examining the impact of writing novel reviews on students' writing ability. This study seeks to fill this gap by investigating the effect of creating novel reviews on students' writing ability and describing the specific aspects of writing that experience development after engaging in this practice. This study used a qualitative approach that involved interviews with 15 respondents enrolled in the English Education program at the fifth-semester level in three different classes. Analysis of the data collected showed a noticeable impact on students' writing skills stemming from their involvement in reviewing novels. There was a significant increase in their vocabulary knowledge, indicating a real impact on linguistic proficiency due to writing novel reviews. This study contributes to shedding light on the unexplored relationship between novel review writing and the improvement of students' writing competence, shedding light on the unexplored aspects of novel review writing